2017
DOI: 10.1136/thoraxjnl-2016-209240
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidities, mortality and causes of death among patients with tuberculosis in Denmark 1998–2010: a nationwide, register-based case–control study

Abstract: In Denmark, TB carries substantial mortality. Among those who die, 12% are reported to die from TB. A high relative mortality among younger adults underscores the importance of continually targeting high-risk TB groups in low-incidence countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 33 publications
2
15
0
1
Order By: Relevance
“…We found a striking difference between Finnish-born cases and those with foreign origins: over one-fifth of Finnish-born cases versus less than 2 % of those with foreign origins had death as outcome, but origin was not independently associated with death in multivariable analysis. Male gender was a risk factor for death as outcome, consistent with our earlier study in Finland [28] as well as previous reports from other low-incidence countries [3,7,29]. We were not able to evaluate reasons for the large risk difference between genders particularly at young age groups, because we did not have data on several risk factors, such as alcohol and substance abuse, the use of immunosuppressive medications and the implementation of directly observed therapy (DOT).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…We found a striking difference between Finnish-born cases and those with foreign origins: over one-fifth of Finnish-born cases versus less than 2 % of those with foreign origins had death as outcome, but origin was not independently associated with death in multivariable analysis. Male gender was a risk factor for death as outcome, consistent with our earlier study in Finland [28] as well as previous reports from other low-incidence countries [3,7,29]. We were not able to evaluate reasons for the large risk difference between genders particularly at young age groups, because we did not have data on several risk factors, such as alcohol and substance abuse, the use of immunosuppressive medications and the implementation of directly observed therapy (DOT).…”
Section: Discussionsupporting
confidence: 78%
“…The majority of TB among the Finnish-born population is in the elderly persons from reactivation of a latent TB infection, reflected by the mean age of 71 years among Finnish-born TB cases in 2017, the highest in the EU/EEA countries [1]. In countries with a high proportion of elderly cases, comorbidities are common, probably contributing to higher mortality observed in TB outcome monitoring [7] and complicating the interpretation of treatment non-success rates between countries.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, there is still a number of people who die before or while on TB treatment. Earlier Danish studies have demonstrated increased long term mortality in TB patients, and a recent Danish study, found the overall hazard ratio of death was 2.45 during two year follow up [2,3]. The study identified increasing age and increasing number of comorbidities to be associated with mortality.…”
Section: Introductionmentioning
confidence: 69%
“…and demographic (low access to health system and food safety, unemployment, precarious housing, etc.) characteristics on the outcome [19][20][21]. Public health and social policies as income distribution are measures that could impact these factors and TB mortality.…”
Section: Table 2 Distribution Of Associated Causes On Death Certificmentioning
confidence: 99%